2014
DOI: 10.5152/balkanmedj.2014.9544
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Total Parathyroidectomy with Autotransplantation versus Subtotal Parathyroidectomy with Routine Addition of Thymectomy to both Groups: Single Center Experience of Secondary Hyperparathyroidism

Abstract: Secondary hyperparathyroidism (sHPT) is a common acquired disorder seen in chronic renal failure. It may result in potentially serious complications including metabolic bone diseases, severe atherosclerosis and undesirable cardiovascular events (1). Parathyroidectomy (PTX) is required in about 20% of patients after 3-10 years of dialysis and in up to 40% after 20 years (2, 3).When medical treatment fails, subtotal parathyroidectomy (subtotal PTX) with a cervical remnant and total parathyroidectomy with autotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 25 publications
2
23
1
2
Order By: Relevance
“…In 1 case (1.1 %), a tense mediastinal hematoma developed after sternotomy when an adenoma grown into the aortopulmonary window was removed, the complication was eliminated using a video-assisted mini-thoracotomy. The frequency of hemorrhagic complications in our study did not exceed the values reported by other authors -from 2 % to 4.3 % (bleeding, neck necrosis, requiring surgical drainage) [14,16].…”
Section: Resultssupporting
confidence: 43%
“…In 1 case (1.1 %), a tense mediastinal hematoma developed after sternotomy when an adenoma grown into the aortopulmonary window was removed, the complication was eliminated using a video-assisted mini-thoracotomy. The frequency of hemorrhagic complications in our study did not exceed the values reported by other authors -from 2 % to 4.3 % (bleeding, neck necrosis, requiring surgical drainage) [14,16].…”
Section: Resultssupporting
confidence: 43%
“…Even if scintigraphy (99mTc-MIBI) is considered the best and most sensitive test [1,3,16], its role in locating all parathyroid glands before surgery is doubtful, being less important when compared with the surgeon's experience [16]. Scintigraphy becomes important in redo procedures for relapsing or persistent hyperparathyroidism, especially when associated with high-resolution cervical ultrasonography [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of improved conventional medical therapy, the need for parathyroidectomy remains high, especially in the group of patients on long-term dialysis with medically refractory sHPT [2,3]. Among surgical indications in sHPT few are generally accepted, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations